ENHANCING THE SKILLS INFERENCE AND A MASTERY THE CONCEPT OF HYDROCARBON BY GUIDED INQUIRY LEARNING MODEL - dita winda vianni; nina kadaritna; emmawaty sofya (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
The aim of this research is enhancing the skills inference and a mastery the concept in guided inquiry model. Population in this research is all the students class X MA N 1 Bandar Lampung first half of the academic year 2011-2012 class X.7 and X.8as a sample. A method of this research is a quasi of his experiments with non equivalent control group design. The effectiveness of learning is measured based on comparative the difference in value pretest and posttest to within the maximum value by the aceh-nias pretes. The result showed the value of average n-gain skill inference for class control and experimentation is -0,65 and 0.61. While the value of average n-gain mastery of the concept of to a class of control and experimentation is 0.18 and 0,55. Based on the testing of hypotheses, it is concluded that the classroom with a model of learning inkuiri terbimbing have the skills inference and a mastery the concept of higher than the classroom with vote was taken.It showed that the model of inquiri terbimbing on any material hydrocarbon more effective in increasing skill inference and a mastery concept students learning than conventionalKeyword: Guided Inquiry Learning, skill inference, mastery concept